2014
DOI: 10.1097/mao.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Bone Bed Formation in Cochlear Implantation Using the Subperiosteal Pocket Technique

Abstract: The subperiosteal pocket technique for cochlear implantation does not require pockets to be drilled in the skull, unlike the standard technique, because bone beds form spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The bone remodeling that can occur around the RS package due to constant pressure exerted on the skull has been identified as a possible stabilizing force. Orhan et al 18 recently described this phenomenon in a cohort of pediatric patients undergoing revision implantation following an initial surgery that used a subperiosteal pocket. Even in the shortest duration between primary and revision surgery (5 months), bone contouring around the RS was seen intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The bone remodeling that can occur around the RS package due to constant pressure exerted on the skull has been identified as a possible stabilizing force. Orhan et al 18 recently described this phenomenon in a cohort of pediatric patients undergoing revision implantation following an initial surgery that used a subperiosteal pocket. Even in the shortest duration between primary and revision surgery (5 months), bone contouring around the RS was seen intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series study reported spontaneous bone bed formation of a subperiosteally secured IRS during revision operations of the CI patients. 14 This is the first study in the literature that demonstrates radiologic evidence of a subperiosteally secured IRS creating its own well in the pediatric population. The retrospective nature of this study did not allow the determination of the depression rate of the IRS on the skull.…”
Section: Discussionmentioning
confidence: 88%
“…To avoid this complication, in the standard technique, a bone bed is created for the internal receiver-stimulator, and various fixation techniques are used. However, by using the subperiosteal pocket technique in paediatric revision cases, we have demonstrated spontaneous bone bed formation, at least six months after surgery 1 . In terms of receiver-stimulator stabilisation, there is no significant difference between spontaneous and created bone bed formation.…”
Section: Introductionmentioning
confidence: 74%